SKETSA ARSITEKTUR ART DECO SEBAGAI IKON KOTA BANDUNG DENGAN MEDIA ALCOHOL INK DAN ACRYLIC - Bakti, Bestin (2017)
Bandung is one of the cities in Indonesia that has a significant Art Deco styled architecture, which is a heritage that we can use as a means of education, as well as a tourist attraction and has very strong characteristics. In this case, the author chooses a school building that still uses the Art Deco style as a form of concern for historical buildings with innovative and creative ways. The author develops the idea of an Art Deco architecture sketch, the visual description of the painting. Then through the stage of contemplation, stimulation and creation process. Which consists of the preparation of tools and materials, sketching, taking the picture of the buildings as the main object, then the execution. The author titles the first work as master shcool with the size of 130 cm x 280 cm, the second work with SMPN 5 Bandung, the third work with Santa Anggela, and the last work with SMAN 20 Bandung. The author is interested in making it four works in drawing made using alcohol ink and acrylic media on canvas, the technique used in works are plaque and aquarelle for it wants to give a dramatic impression on the work, the colors used bright colors that intend to bring enlightenment to the world of education. To find out the descriptions of the work, and to visualize it aesthetically, the "Art Deco" styled schools become the main objects of creation of the work, it started from the idea of work. The visual description of the work is in conformity with the rules of the creation of drawing artwork with clear sources.;---Bandung merupakan salah satu kota di Indonesia yang memiliki bangunan Arsitektur bergaya Art Deco yang signifikan, merupakan harta warisan yang bisa dijadikan sarana edukasi, maupun objek wisata. serta memiliki ciri dan karakteristik yang sangat kuat. Dalam hal ini, penulis memilih bangunan sekolah yang masih menggunakan bangunan bergaya Art Deco, sebagai wujud kepedulian akan bangunan bersejarah dengan cara inovatif dan kreatif. Penulis mengembangkan gagasan mengenai sketsa arsitektur Art Deco, deskripsi visualisasi karya seni lukis. Kemudian melalui tahap kontemplasi, stimulasi dan proses penciptaan. Yang terdiri dari persiapan alat bahan, sketsa, pengambilan gambar bangunan sebagai objek utama, kemudian berkaya. Karya pertama berjudul master shcool dengan ukuran 130 cm x 280 cm, karya kedua SMPN 5 Bandung, karya ketiga Santa Anggela, dan karya terakhir SMAN 20 Bandung. Penulis tertarik untuk menjadikannya empat buah karya dalam menggambar yang dibuat menggunakan media alcohol ink dan acrylic di atas kanvas, teknik yang digunakan pada karya menggunakan teknik plakat dan aquarel, hal ini ingin memberikan kesan dramatis pada karya, warna yang digunakan warna-warna cerah yang bermaksud membawa pencerahan pada dunia pendidikan. Untuk mengetahui mendeskripsikan karya, serta memvisualisasikannya secara estetis, sekolah bergaya "Art Deco" manjadi objek utama pada pembuatan karya, hal tersebut berawal dari ide bekarya. Deskripsi visual pada karya sudah sesuai dengan peraturan pembuatan karya menggambar dengan sumber-sumber yang jelas.